The allowable stress method is the basis of the modern method of calculating building structures according to limit states - Pichugin, Sergii (Academic journal. Industrial Machine, Building Civil Engineering, 2022)
The article consistently examines the evolution of building construction calculation methods and their reflection in regulatory documents for the period from the 17th-18th centuries to the middle of the 20th century. Attention is drawn to the continuity of the method of limit states and the method of allowable stresses, which dominated the calculations of building structures until the 1950s. It is noted that foreign experience was taken into account when developing the first domestic design codes. A comparative analysis of the codes for calculating building structures based on allowable stresses with modern design codes is carried out. The general conclusion is substantiated that the method of allowable stresses, despite all its shortcomings, over the 200-year period of application still ensured the necessary reliability and safety of construction objects around the world. In the background of the method, a large and valuable baggage of scientific results was acquired, which were later laid as the basis of a new method of limit states